Geopolitics of tabula rasa: Persian garden and the idea of city - Khosravi, Hamed (Journal of Architecture and Urbanism, 2014)
Historically Persian Garden symbolizes a well-ordered landscape, which is mostly associated with the leisure and enjoyment of the kings. However here it is read as inevitable form of built environment within the Iranian plateau. Garden (bāgh) not only creates a minimum condition for a life, but it is the spatial device through which the power of the sovereign dominates the territory. In the harsh landscape of Iran gardens were micro-cosmos; camps that protected life and let it flourish within the tabula rasa. In such a condition any distinction between various forms of life ceases to exist and life becomes the ‘ideal life’, kings represent God and city becomes paradise.